2013
DOI: 10.1158/1535-7163.mct-12-0988
|View full text |Cite
|
Sign up to set email alerts
|

Human Anti-Macrophage Migration Inhibitory Factor Antibodies Inhibit Growth of Human Prostate Cancer Cells In Vitro and In Vivo

Abstract: Macrophage migration inhibitory factor (MIF) is a proinflammatory cytokine, originally discovered for its eponymous effect and now known for pleiotropic biologic properties in immunology and oncology. Circulating MIF levels are elevated in several types of human cancer including prostate cancer. MIF is released presumably by both stromal and tumor cells and enhances malignant growth and metastasis by diverse mechanisms, such as stimulating tumor cell proliferation, suppressing apoptotic death, facilitating inv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
69
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 42 publications
2
69
0
Order By: Relevance
“…Human monoclonal anti-MIF Abs BaxB01, BaxG03, and BaxM159 were shown to neutralize MIF functional activity in cell-based assays and to be protective in animal models (30,31). However, surface plasmon resonance (SPR; Fig.…”
Section: Two Conformational Isoforms Of Mif Are Immunologically Distinctmentioning
confidence: 99%
See 1 more Smart Citation
“…Human monoclonal anti-MIF Abs BaxB01, BaxG03, and BaxM159 were shown to neutralize MIF functional activity in cell-based assays and to be protective in animal models (30,31). However, surface plasmon resonance (SPR; Fig.…”
Section: Two Conformational Isoforms Of Mif Are Immunologically Distinctmentioning
confidence: 99%
“…We recently described the fully human mAbs BaxB01, BaxG03, and BaxM159 that effectively inhibit the biological activity of MIF in vivo and in vitro (30,31). These Abs are specific for two distinct epitopes (aa 50-68 or 86-102), which form a b-barrel structure containing the highly conserved 57 Cys-Ala-Leu-Cys 60 -motif (30); this forms the catalytic motif of the thiol protein oxidoreductase linked to MIF's biologic function (32)(33)(34).…”
mentioning
confidence: 99%
“…Human macrophage migration inhibitory factor (HuMIF) has been implicated in a broad array of conditions associated with inflammation, including autoimmunity, cell proliferation, angiogenesis, and tumorigenesis (12)(13)(14)(15). Increased expression of HuMIF has been reported in several cancers, including prostate cancer (16)(17)(18). Studies show high expressers of HuMIF have a heightened risk of prostate cancer, as well as a significant increase in prostate cancer progression and drug resistance (17)(18)(19)(20)(21)(22)(23).…”
mentioning
confidence: 99%
“…Increased expression of HuMIF has been reported in several cancers, including prostate cancer (16)(17)(18). Studies show high expressers of HuMIF have a heightened risk of prostate cancer, as well as a significant increase in prostate cancer progression and drug resistance (17)(18)(19)(20)(21)(22)(23). Several clinical studies have shown HuMIF production correlates with both tumor aggressiveness and metastatic potential (23,24).…”
mentioning
confidence: 99%
“…Adhesion, migration and tumor cell invasivenessespecially related to E-cadherin adhesion molecule; 3. Tumor angiogenesis -which can be immunochemically evaluated by CD34 expression [5,6].…”
Section: Introductionmentioning
confidence: 99%